Uterine inertia in a cat (Queen) - JADHAV, P T; YADAV, G U; BHOKRE, A P; MARKANDAYA, N M (The Indian Journal of Animal Reproduction, 2002)
A rare case of maternal dystocia due to secondary uterine inertia in a cat has been reported in the presentpaper.
Keywords: Uterine inertia; dystocia; cat